2021
DOI: 10.20961/agrotechresj.v5i2.54333
|View full text |Cite
|
Sign up to set email alerts
|

Response of Basil (Ocimum basilicum) Growth and Yield to Planting Densities and Row Arrangements in Tomato-Basil Intercropping System

Abstract: Wondo Genet area, which is located in the Sidama zone of south Ethiopia, is characterized by a rapidly increasing human population and scarcity of arable land per household. There is a need for developing an efficient cropping system to use the limited land efficiently and to enhance food security. An experiment was, therefore, was conducted at Wondo Genet Agricultural Research Center under irrigated during the 2018 cropping season to examine the growth and yield of sweet basil under different planting densiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…However, Islam et al, (2011), Alabi et al, (2014), andThakur et al, (2018) have reported maximum plant height values for higher population densities, which might be attributed to heavy shading in higher population densities that triggered plants to compete for solar radiation, resulting in increased internodal length. Similar results have been reported by Pereira et al, (2016) and Mamo (2021) in their studies on intercropping with basil.…”
Section: Resultssupporting
confidence: 91%
“…However, Islam et al, (2011), Alabi et al, (2014), andThakur et al, (2018) have reported maximum plant height values for higher population densities, which might be attributed to heavy shading in higher population densities that triggered plants to compete for solar radiation, resulting in increased internodal length. Similar results have been reported by Pereira et al, (2016) and Mamo (2021) in their studies on intercropping with basil.…”
Section: Resultssupporting
confidence: 91%